Synthesis, structure, and optoelectronic properties of a new twistacene 1,2,3,4,6,13-hexaphenyl-7 : 8,11 : 12-bisbenzo-pentacene - Xiao, Jinchong (2012)
We report the synthesis, optical and electrochemical properties, as well as the fabrication of